RECTIFYING DEVELOPABLE SURFACE OF TIMELIKE BIHARMONIC CURVE IN THE LORENTZIAN HEISENBERG GROUP HEIS3 - Korpinar, T.; Turhan, E. (Turkic World Mathematical Soc, 2012)
In this paper, we study in particular developable surfaces, a special type of ruled surface in the Lorentzian Heisenberg group Heis(3). We find out explicit parametric equations of rectifying developable of timelike biharmonic curve in the Lorentzian Heisenberg group Heis(3). Additionally, we illustrate three figures of our main theorem.
Keywords: Heisenberg group; biharmonic curve; helix; developable surface